2021
DOI: 10.1002/jcp.30529
|View full text |Cite
|
Sign up to set email alerts
|

TGF‐β signaling: A recap of SMAD‐independent and SMAD‐dependent pathways

Abstract: Transforming growth factor-β (TGF-β) is a proinflammatory cytokine known to control a diverse array of pathological and physiological conditions during normal development and tumorigenesis. TGF-β-mediated physiological effects are heterogeneous and vary among different types of cells and environmental conditions. TGF-β serves as an antiproliferative agent and inhibits tumor development during primary stages of tumor progression; however, during the later stages, it encourages tumor development and mediates met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(46 citation statements)
references
References 299 publications
(471 reference statements)
1
45
0
Order By: Relevance
“…There was a division among the researchers, some believed that TGF-β could be tumour promoter, and some ended up saying that it has a role in tumour suppression. Dysregulation of TGF-β signaling hijacks the complexes of biological functions that plays critical role in developmental processes and tumorigenesis, thus emerges as a promising signaling pathway to be targeted for the anticancer drug development at preclinical and clinical stages ( Aashaq et al, 2021 ). TGF-β signaling pathway has a decisive and dual role in the human cancer progression.…”
Section: Introductionmentioning
confidence: 99%
“…There was a division among the researchers, some believed that TGF-β could be tumour promoter, and some ended up saying that it has a role in tumour suppression. Dysregulation of TGF-β signaling hijacks the complexes of biological functions that plays critical role in developmental processes and tumorigenesis, thus emerges as a promising signaling pathway to be targeted for the anticancer drug development at preclinical and clinical stages ( Aashaq et al, 2021 ). TGF-β signaling pathway has a decisive and dual role in the human cancer progression.…”
Section: Introductionmentioning
confidence: 99%
“…Then, seven genes, including BMP2, GSTA1, GSTA3, BST1, S100A9, TTR, and GATM, were identified as the targets of the YSHS granule in the treatment of ADR-induced FSGS by Real-time PCR analysis. Among these validated targets of YSHS, BMP2 belongs to the TGF-β superfamily, has a similar ligand structure, similar receptor-binding proteins, and similar downstream signaling cascades to TGF-β1 ( Aashaq et al, 2022 ). Many researches demonstrated that BMP2 plays an important role in the occurrence, development, and outcome of renal interstitial fibrosis ( Yang et al, 2009 ; Yang et al, 2011 ; Simone et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…SMADs play an important role as transducers of cellular responses after TGF-β receptor engagement 11 . To address the role of these transcription factors inTGF-β-triggered EMT, we isolated endometrial epithelial cells from tamoxifen-inducible double SMAD2/3 knock-out mice (Cre:ER +/− ;SMAD2 f/f ;SMAD3 f/f ).…”
Section: Loss Of Cell Polarity Caused By Absence Of Ecm Impairs Tgf-β...mentioning
confidence: 99%
“…The SMAD family consists of nine members, which form 3 subfamilies: receptor-activated (R-)SMADs (SMAD1, SMAD2, SMAD3, SMAD5, SMAD8 and SMAD9), a single common-mediator (Co-)SMAD (SMAD4) and two inhibitory (I-)SMADs (SMAD6 and SMAD7). TGF-β also induces non-SMAD pathways, including mitogen-activated protein kinase (MAPK), phosphoinositide-3kinase (PI3K) and Rho GTPases 11 .…”
Section: Introductionmentioning
confidence: 99%